2019
DOI: 10.1039/c9ra04388h
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of JNK-1/ β-catenin signaling byLactobacillus casei, inulin and their combination in 1,2-dimethylhydrazine-induced colon cancer in mice

Abstract: Colon cancer is a complex disease that involves numerous genetic alterations that change the normal colonic mucosa into invasive adenocarcinoma. In the current study, the protective effects of inulin (prebiotic), Lactobacillus casei (L. casei, probiotic) and their combination (synbiotic) on 1,2dimethylhydrazine (DMH)-induced colon cancer in male Swiss mice were evaluated. Animals were divided into: Control group, DMH-treated group, DMH plus inulin, DMH plus L. casei and DMH plus inulin plus L. casei-treated gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 79 publications
2
38
0
3
Order By: Relevance
“…To the best of our knowledge, no study has been conducted to apply the antitumor activity and protective effects of L. gasseri ATCC 33323 on modulating β-catenin expression in gastric epithelial cells stimulated by H. pylori strains. There are only a few reports which used L. rhamnosus (LGG) and L. casei to down-regulate β-catenin expression, thereby preventing the initiation and progression of colon cancer [54,55]. In line with these studies, our results also showed that L. gasseri ATCC 33323 significantly decreased the expression of β-catenin in AGS cells cocultured with clinical H. pylori strains.…”
Section: Discussionsupporting
confidence: 85%
“…To the best of our knowledge, no study has been conducted to apply the antitumor activity and protective effects of L. gasseri ATCC 33323 on modulating β-catenin expression in gastric epithelial cells stimulated by H. pylori strains. There are only a few reports which used L. rhamnosus (LGG) and L. casei to down-regulate β-catenin expression, thereby preventing the initiation and progression of colon cancer [54,55]. In line with these studies, our results also showed that L. gasseri ATCC 33323 significantly decreased the expression of β-catenin in AGS cells cocultured with clinical H. pylori strains.…”
Section: Discussionsupporting
confidence: 85%
“…Ali et al reported that L. casei probiotic supplementation in mice with 1,2dimethylhydrazine-induced colon cancer significantly reduced the number of aberrant crypt foci compared with that in untreated animals. Furthermore, by upregulating the expression of phosphorylated JNK-1, L. casei regulated the expression of β-catenin and phosphorylated GSK3β, leading to significant protective effects against colon cancer (Ali et al, 2019). Sakatani and others have demonstrated that a L. brevis-derived polyphosphate significantly promoted the activation of the ERK signaling pathway, expression of cleaved PARP, and the ratio of cleaved PARP/PARP in SW620 colon cancer cells and mice bearing SW620 tumor xenografts.…”
Section: Probiotics and Colon Cancer In Animal Studiesmentioning
confidence: 99%
“… 3 Inulin, a β-(2–1) linked fructan polymer, can be found in chicory roots, beet roots, leeks, and other natural sources. 13 In addition, as a prebiotic additive in food, inulin has been found to effectively protect mice from developing colon cancer, 14 directly modulate immune responses, and attenuate proinflammatory responses in dendritic cells. 13 Microcrystalline cellulose (MCC, IDF), a novel food additive found in hardwood, softwood, cotton linter, and lignocellulosic materials, especially agricultural residues, 15 can promote the growth of specific flora in the gut and regulate the host microbiota.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 Inulin and MCC are both plant source fibers that are used as functional additives of yogurt, sausages, DF supplements during pregnancy, and so forth and play an important role in the food and health product industry. 14 In animals, dietary inulin and MCC cannot be hydrolyzed by endogenous enzymes, but they are readily fermented by microbes in the colon and caecum and are beneficial to bifidobacterial growth in the gut. 6 The combined soluble fibers, with high viscosity and fermentability, have been found to attenuate systemic inflammation, promote intestinal microbiota homeostasis, and improve the intestinal morphological integrity of mice suffering from obesity induced by a high-fat diet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation